Evaluation of the Visual Learning Application for Mathematics using Holography Display for the topic on Shape and Space - Tyng K.S.; Zaman H.B.; Mohamad U.H.; Ahmad A. (Politeknik Negeri Padang, 2024)
Mathematics is an important foundation in the life of an individual. The problems associated with learning Mathematics that are commonly encountered, are due to factors such as: abstract phenomena and concepts, low imagination, and lack of understanding of the concepts being studied. Thus, the purpose of this study is to help primary school children improve their ability to recognise 3D shapes that are abstract phenomena. This paper presents the Effectiveness Usability Evaluation of the Visual Learning Application for Mathematics using Holography Display for the topic on Shape and Space called MEL-VIS. This study was conducted on eighty (80) primary school students. The results of the study showed that learning about 3D shapes with the E-Visual MEL-VIS application prototype is more effective than traditional methods. 2023, Politeknik Negeri Padang. All rights reserved.